The Technological Development of the Bow and the Crossbow in the Later Middle Ages - Gorman, Stuart (School of Histories and Humanities, 2016)
This thesis explores the complexity of the design and development of the bow and the crossbow in the Later Middle Ages. The data used in this study were primarily archaeological, supplemented by some textual and artistic evidence. Information on over two hundred bows and crossbows was collected for the analysis in this study. The methodology of this work was primarily comparative: bows and crossbows were compared to each other across and within centuries and regions, to chart how the weapons developed over time. The main thrust of this thesis was to argue for a more complex understanding of the bow and the crossbow. Historians have generally not engaged with the complex mechanics involved in the operation of a bow or crossbow. An understanding of these mechanics offers valuable insight into why these weapons were designed the way they were, as well as highlighting what aspects of these weapons were truly significant. For example, longbow discussions have generally focused on the length of the weapon, but thickness was actually a more important factor in determining how powerful, and therefore deadly, a longbow was. This thesis includes information on longbows from as early as prehistory and as late as the Mary Rose. These data were used both to show that length was not the most important factor in longbow design – the prehistoric bows were very long but would have been comparably weak – and to show that powerful longbows were made in the High Middle Ages, but were still weaker than the Mary Rose longbows. This thesis also challenges the idea that depictions of the longbow in medieval art could be used to reliably provide specific insight into the weapon's design or development, but could provide information on other aspects, such as how bows and crossbows were handled. The study of the medieval crossbow focused on surviving examples from the fourteenth through to the sixteenth centuries. No clear narrative for the weapon’s development could be found; instead, crossbows developed into an increasingly complex variety of weapons as the Middle Ages became the early modern period. There was some standardisation to the weapon’s design in the fifteenth century, both in composite and steel crossbows, but, while the composite lathe barely changed in the sixteenth century, the steel crossbow diversified into a range of different styles of crossbows, all of which came in different sizes and shapes. There should be a typology to describe the diversity of these crossbows, in order to allow historians to talk about the weapon in a more specific and meaningful way. 3 In conclusion, this thesis has advocated for greater complexity and detail in the study of the bow and crossbow. The simplification of these weapons has led to much misunderstanding about their performance and use in medieval armies. Craftsmen, soldiers, and commanders all played a role in determining what kinds of weapons were used at a given time or place, and understanding the reasons for the variety of these weapons available during the Later Middle Ages could provide new and significant insight into medieval and early modern warfare.
Keywords: Crossbow; Middle Ages